The challenges of adoptive cell transfer in the treatment of human renal cell carcinoma - Strizova, Zuzana; Bartunkova, Jirina; Smrz, Daniel (Cancer immunology, immunotherapy, 2019)
Renal cell carcinoma (RCC) is one of the most lethal urologic malignancies. Its incidence continues to rise worldwide with a rate of 2% per year. Approximately, one-third of the RCC patients are diagnosed at advanced stages due to the asymptomatic nature of its early stages. This represents a great hurdle, since RCC is largely chemoresistant/radioresistant, and targeted therapy of mRCC still has limited efficacy. The 5-year survival rate of metastatic RCC (mRCC) is only around 10%. Adoptive cell transfer (ACT), a particular form of cell-based anticancer immunotherapy, is a promising approach in the treatment of mRCC. The vaccination principle, however, faces unique challenges that preclude the efficacy of ACT. In this article, we review the main challenges of ACT in the treatment of mRCC and describe multiple methods that can be used to overcome these challenges. In this respect, the ultimate purpose of this review is to provide a descriptive tool by which to improve the development of novel protocols for ACT of mRCC.
Keywords: Adoptive Transfer; Carcinoma, Renal Cell; lidé; PECAM; karcinom z renálních buněk; míra přežití; Renal cell carcinoma; Kidney Neoplasms; PIVAC 18; imunoterapie; zvířata; Humans; Survival Rate; Immunotherapy; převzatá imunita; Peritumoral lymphocytes; Tumor-infiltrating lymphocytes; ACT; nádory ledvin; Animals